A Study on the Indigenous Methods of Processing Milk in Niger - GAGARA, MARIAMA; SESSOU, PHILIPPE; AHOUNOU, GBÊNAGNON SERGE; AZOKPOTA, Paulin; YOUSSAO ABDOU KARIM, ISSAKA; GOURO, ABDOULAYE SOUMANA; FAROUGOU, SOUAÏBOU (My University, 2019)
The purpose of this study was to identify the methods of processing and preserving of local milk within the area of Liptako-Gourma in Niger. A survey was conducted and data were collected from 600 people involved in dairy sector, comprising of 59% producers , 28.7% collectors and 12.3% processors. The study also revealed two main methods of milk processing that is pasteurization and fermentation comprising of natural/ spontaneous fermentation done by 42.9% and fermentation method by backslopping practiced by 57.10% of processors. In addition, four methods of preserving milk were identified, including the cooling of raw milk, pasteurized or fermented milk, the pasteurization of raw milk itself for sale or for processing, the fermentation of raw milk or pasteurized milk and the addition of guinea pepper pods to fermented milk. Milk processing and preserving technology remains traditional with no compliance to hygiene good practices and the use of old material being limited most often to the strict minimum. Due to these results, attention should be paid to the training of the processors on hygiene and good practices at all levels of the local milk industry in order to improve traditional methods related to the processing and preserving of local milk and thus raising the quality of the dairy products in terms of microbiological safety
Keywords: Indigenous Methods; Milk; Processors; Pocessing; Preservation; Survey